Research on the scalability of parallel community detection algorithms - Qiang LIU; Yan JIA; Binxing FANG; Bin ZHOU; Yue HU; Jiuming HUANG (Tongxin xuebao)
The social network often contains a large amount of information about users and groups,such as topic evolution mode,group aggregation effect,the law of information dissemination and so on.The mining of these information has become an important task for social network analysis.As one characteristic of the social network,the group aggregation effect is characterized by the community structure of the social network.The discovery of community structure has become the basis and key point of other social network analysis tasks.With the rapid growth of the number of online social network users,the traditional community detection methods have been difficult to be used,which contributes to the development of parallel community detection technology.The current mainstream parallel community detection methods,including Louvain algorithm and label propagation algorithm,were tested in the large-scale data sets,and corresponding advantages and disadvantages were pointed out so as to provide useful information for later applications.